Pengaruh Mutasi Kerja, Promosi Jabatan Dan Rolling Jabatan Terhadap Prestasi Kerja Personel Kepolisian (Pada Kantor Satuan Polisi Pamong Praja Kota Malang) - Sandi Agung Mahardika; Muhammad Ridwan Basalamah; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study was conducted to determine the effect of job transfers, promotions, and job roll-overs on employee performance (at the Malang City Civil Service Police Unit). This research uses explanatory research and quantitative approach. The sample in this study included all employees at the Malang City Civil Service Police Unit, a total of 90 respondents. To solve the problem in this research, using validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. The study used multiple linear regression analysis with the help of SPSS 20. The results of this study simultaneously affect the variable of Employee Achievement at the Malang City Civil Service Police Unit Office, the Job Mutation variable affects the Employee Achievement variable at the Malang City Civil Service Police Unit Office, the Position Promotion variable affects the Employee Achievement variable at the Civil Service Police Unit Office Malang City, Rolling Position has an effect on the variable of Employee Achievement at the Civil Service Police Unit Office of Malang City. Keywords: Job Performance, Job Mutation, Promotion, Position Rolling